Encapsulation of adipose-derived stem cells and transforming growth factor-beta 1 in carrageenan-based hydrogels for cartilage tissue engineering - Rocha, Pedro M. (2011)
Tissue engineering (TE) is an emerging field for the regeneration of damaged tissues. The combination of hydrogels with stem cells and growth factors (GFs) has become a promising approach to promote cartilage regeneration. In this study, carrageenan-based hydrogels were used to encapsulate both cells and transforming growth factor-b1 (TGF-b1). The ATDC5 cell line was encapsulated to determine the cytotoxicity and the influence of polymer concentration on cell viability and proliferation. Human adipose-derived stem cells (hASCs) were encapsulated with TGF-b1 in the hydrogel networks to enhance the chondrogenic differentiation of hASCs. Specific cartilage extracellular matrix molecules expression by hASCs were observed after 14 days of cultures of the constructs under different conditions. The k-carrageenan was found to be a suitable biomaterial for cell and GF encapsulation. The incorporation of TGF-b1 within the carrageenan-based hydrogel enhanced the cartilage differentiation of hASCs. These findings indicate that this new system for cartilage TE is very promising for injectable thermoresponsive formulation applications.